DYNAMIC ANALYSIS FOR SELF –LOCKING TRAPEZOIDAL ORIGAMI SHELL STRUCTURE - Makentheran, Kayilass Hari Nair (IRC, 2020)
This research is done based on the composite fiber used in the concept of origami. The ancient art of origami comes as a spur for the design and study of such structures. Rigid origami can be made on a human scale due to its ability to enable folding without deformation of its shape. These can be done in for applications in engineering using active origami designs for architectural, automotive industry etc. absorbing impact abilities are very sought in many applications, using in automotive industries and aviation requires this trait to increase the safety of the passengers. Therefore, using fiber reinforced composite using origami shape or design will be used as a shell structure of the vehicles, although the characteristics are light, but it has very high stiffness and low in brittle which is unfavourable for absorbing impacts